Bibliometric Analysis of Open Innovation Research Trends in the Technology Industry - Judijanto, Loso; Nampira, Ardi Azhar; Safitri, Telma Anis (West Science Business and Management, 2025)
Open innovation has emerged as a critical paradigm in the technology industry, enabling firms to leverage external knowledge and collaborative networks to accelerate innovation and enhance competitiveness. This study conducts a comprehensive bibliometric analysis of open innovation research from 2003 to 2024 using data extracted from the Scopus database. By employing VOSviewer software, the study visualizes keyword co-occurrences, temporal trends, author co-citation networks, and international collaboration patterns. The results reveal that the field has matured significantly, with foundational themes such as knowledge transfer, absorptive capacity, and product development remaining central. Concurrently, emerging topics including artificial intelligence, business models, sustainability, and digital ecosystems reflect the evolving relevance of open innovation in addressing contemporary technological and societal challenges. Influential scholars like Chesbrough, Gassmann, and Bogers have played pivotal roles in shaping the intellectual landscape, while countries such as the United States, Germany, China, and Italy lead in global collaboration. The study highlights the multidimensional and dynamic nature of open innovation research and offers insights for academics and practitioners aiming to navigate the next frontier of innovation management.